Orthodontically Management of Non-extraction Class-II Division 2 Malocclusion- A Case Report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
A patient of 21 years old presented with Class II division 2 malocclusion and deep overbite, was treated by fixed orthodontic therapy. After completion of the treatment, extreme deep bite was corrected, proclination of upper anterior teeth and patient was satisfied with new position of his upper anterior teeth. DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16166 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 46-47